2012
DOI: 10.1002/bit.24538
|View full text |Cite
|
Sign up to set email alerts
|

pH, redox potential and local biofilm potential microenvironments within Geobacter sulfurreducens biofilms and their roles in electron transfer

Abstract: The limitation of pH inside electrode-respiring biofilms is a well-known concept. However, little is known about how pH and redox potential are affected by increasing current inside biofilms respiring on electrodes. Quantifying the variations in pH and redox potential with increasing current is needed to determine how electron transfer is tied to proton transfer within the biofilm. In this research, we quantified pH and redox potential variations in electrode-respiring Geobacter sulfurreducens biofilms as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
122
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 125 publications
(131 citation statements)
references
References 45 publications
8
122
1
Order By: Relevance
“…Yu et al reported that the highest mean SOC density (209.9 t C ha -1 ) was recorded from a wetland ecosystem and the lowest (29.0 t C ha -1 ) from a desert ecosystem in China [16]. Due to the greatly reduced supply of O 2 to soil and the decreased organic carbon mineralization rates in the natural wetland, the natural wetland shows a high content of soil organic carbon in the anaerobic environment [17]. In the anaerobic environment, anaerobic microorganisms as well as photosynthesis by submerged macrophytes can create high pH values in the aquatic environment [18].…”
Section: Resultsmentioning
confidence: 99%
“…Yu et al reported that the highest mean SOC density (209.9 t C ha -1 ) was recorded from a wetland ecosystem and the lowest (29.0 t C ha -1 ) from a desert ecosystem in China [16]. Due to the greatly reduced supply of O 2 to soil and the decreased organic carbon mineralization rates in the natural wetland, the natural wetland shows a high content of soil organic carbon in the anaerobic environment [17]. In the anaerobic environment, anaerobic microorganisms as well as photosynthesis by submerged macrophytes can create high pH values in the aquatic environment [18].…”
Section: Resultsmentioning
confidence: 99%
“…Large pH differences have been recorded in Pseudomonas biofilms, where a difference of 1.4 pH units was measured across distances of 50 m (20). Further pH shifts have been seen across a variety of distances in a range of biofilms grown under different conditions (21)(22)(23). However, in all these cases, the pH shifts are associated with near neutral conditions, and as such, the logarithmic nature of the pH scale means that the modulation of internal pH in response to alkaline conditions represents a significantly more difficult challenge to the microorganisms concerned.…”
mentioning
confidence: 97%
“…Construction and pulling of the individual graphite microelectrodes has been detailed previously. 15 The two microelectrode tips were positioned ∼1 mm apart with the lower one to be used as the microelectrode tip. The higher graphite microelectrode was used as the counter electrode.…”
Section: Methodsmentioning
confidence: 99%
“…After it was visually confirmed that the reactor volume remained clear and unchanged, approximately 20 mL of G. sulfurreducens inoculum was added to the reactor following a previously published method. 15 An immediate current response was observed and, after half a day, the reactor was switched to operate in continuous mode until the end of the experiment. Once a maximum current was observed from the electrode-biofilm, we prepared microelectrodes for insertion into the biofilm reactor.…”
Section: Methodsmentioning
confidence: 99%